Hubungan Persepsi Tentang Kematian dan Tingkat Kecemasan pada Lansia di Desa - Ginting, Agustaria; Elvina Pakpahan, Rotua; Melissa Augeretha Simanjuntak (Jurnal Kesehatan, 2024)
The elderly tend to be more susceptible to deterioration of biological functions, including anxiety about the end of their lives and death. Anxiety can occur if the elderly live alone and far from their families, thus giving rise to the perception of death. Research conducted by Irwan (2022) showed that of the 98 elderly with a negative perception of 56.1% and a moderate level of anxiety of 76.5%. This study aims to identify the relationship between the perception of death and anxiety levels in the elderly in the East Siantar District Asuhan Village in 2023. The research is analytical and has a cross-sectional design. The research population was 3,200 elderly people with a sample of 70 elderly people, where the sample was taken using a purposive sampling technique with the inclusion criteria of people aged 60 and over. Data collection was conducted directly using interview techniques and questionnaire distribution. The study found that the average score of perception of death was 51.69, with a standard deviation of 8,590 scores. In comparison, the average anxiety level was 7.24 scores, with a standard deviation of 1,937 scores. The results of the product moment found that the value of p-value = 0.001 (p<0.05) with a correlation value of 0.585 with a positive pattern, meaning that there is a relationship between the perception of death and the level of death in the elderly, where the higher the perception of the elderly about death, the more anxiety about death occurs. It means that there is a strong relationship between the perception of death and the level of anxiety in the elderly in East Siantar District Asuhan Village in 2023.